1985
DOI: 10.1128/aem.49.4.778-781.1985
|View full text |Cite
|
Sign up to set email alerts
|

Virus persistence in groundwater

Abstract: More than 50% of the outbreaks of waterborne disease in the United States are due to the consumption of contaminated groundwater. An estimated 65% of the cases in these outbreaks are caused by enteric viruses. Little, however, is known about the persistence of viruses in groundwater. The purpose of this study was to determine whether measurable chemical and physical factors correlate with virus survival in groundwater. Groundwater samples were obtained from 11 sites throughout the United States. Water temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
134
2
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(148 citation statements)
references
References 10 publications
7
134
2
5
Order By: Relevance
“…Although coronavirus inactivation rates are difficult to compare between studies, one finding this study shares with previous work is that temperature is an important factor influencing viral survival. Temperature and incubation time were significant predictors of viral reduction in this study, which is consistent with previous findings on viral survival in water (Yates et al, 1985;Hurst et al, 1989;Enriquez et al, 1995). Water type was also a significant predictor of the rate of viral reduction, with greater reduction in pasteurized settled sewage as compared to reagent-grade water.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although coronavirus inactivation rates are difficult to compare between studies, one finding this study shares with previous work is that temperature is an important factor influencing viral survival. Temperature and incubation time were significant predictors of viral reduction in this study, which is consistent with previous findings on viral survival in water (Yates et al, 1985;Hurst et al, 1989;Enriquez et al, 1995). Water type was also a significant predictor of the rate of viral reduction, with greater reduction in pasteurized settled sewage as compared to reagent-grade water.…”
Section: Discussionsupporting
confidence: 91%
“…In pasteurized settled sewage spiked with MHV, pH declined over a period of weeks (data not shown), but remained within the range of stability for these viruses, suggesting that it may not have been a significant factor in declining viral infectivity. The lack of pH effect on virus survival is consistent with previous studies (Yates et al, 1985). Chemical constituents found in sewage may have antiviral activity (Sobsey et al, 1980), and previous investigations have found that virus survival in water is influenced by high molecular weight dissolved matter (Noble and Fuhrman, 1997), which is present at higher concentrations in sewage.…”
Section: Discussionsupporting
confidence: 90%
“…The dsDNA-tailed bacteriophages are almost certainly the most abundant group of organisms in the biosphere with a global population estimated to stand at c. 10 31 (Hendrix et al, 1999). It has been shown by many investigators that viral pathogens are more recalcitrant in the natural environment than their cellular hosts (Hurst et al, 1980;Yates et al, 1985;Abad et al, 1994;Baggi et al, 2001;Lucena et al, 2003;Skraber et al, 2004). Specific studies with Stx phages have demonstrated their increased survival in the environment compared with their bacterial hosts, including increased resistance to pasteurization and chlorination (Muniesa et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The poliovirus is inactivated more readily than the hepatitis A virus by heating and storage treatments used to prepare manure for spreading on lands (Stramer and Cliver, 1984;Deng and Cliver, 1992). However, once the environment is contaminated, the poliovirus survives for weeks to months in groundwater (Yates et al, 1985;Gordon and Toze, 2003) and in soil (Yeager and O'Brien, 1979;Hurst et al, 1980). This virus has also been shown to persist for weeks to months on vegetables irrigated by spraying or flooding with contaminated waters (Tierney et al, 1977).…”
Section: Poliovirusmentioning
confidence: 99%